2007
DOI: 10.1111/j.1741-1130.2007.00117.x
|View full text |Cite
|
Sign up to set email alerts
|

The Male Workforce in Intellectual Disability Services

Abstract: Staff shortages are predicted in community social care sector services for people with intellectual disabilities (ID). One option is to attract more men to the workforce, which would also counter the present sex‐ratio (gender) imbalance among workers. Potential strategies for recruitment could be identified by analyzing the characteristics and experiences of the male staff currently employed in such jobs. To do this, the authors undertook three studies: (1) a census of 653 staff in statutory services within on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 14 publications
2
15
0
Order By: Relevance
“…It offers a starting point to frame why more male care staff working in the sector should be a sector wide goal. There may well be a relationship between male staff and positive outcomes for male clients, a finding also reported by McConky et al (2007).…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…It offers a starting point to frame why more male care staff working in the sector should be a sector wide goal. There may well be a relationship between male staff and positive outcomes for male clients, a finding also reported by McConky et al (2007).…”
Section: Discussionmentioning
confidence: 61%
“…Based upon a combination of individual belief systems, duty of care and perceived professional boundaries, these are interdependent and deeply complex issues. The literature has acknowledged some of these gender-specific issues for support staff (Thompson et al 1997;McConky et al 2007); however, a wider appreciation of masculinity theory and its potential for understanding gender-relations and genderhierarchies is absent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Providing opportunities for direct contact with those being supported and the staff supporting them, such as service visits (McConkey, McAuley, Simpson, & Collins, 2007) and opportunities for placements/voluntary work/shadowing to potential employees (Owen & Standen, 2007; Sutten et al, 2015), have been identified in other caring contexts as important ways of recruiting staff with the right values, with realistic expectations, and who are committed to the area of work, as well as increasing opportunities to recruit from a more diverse workforce (Alink, Euser, Bakermans‐kranenburg, & van IJzendoorn, 2014; Werner, 2011). Our results indicate the importance of ensuring that those undertaking such opportunities are well‐supported and supervised.…”
Section: Discussionmentioning
confidence: 99%